Fiber recruitment drives a phase transition of cell polarization at a critical cell spacing in matrix-mediated tissue remodeling - Xiangjun Peng; Yuxuan Huang; Wenyu Kong; Yanan Du; Elliot L. Elson; Xi-Qiao Feng; Guy M. Genin (Proceedings of the National Academy of Sciences, 2025)
Biological tissues exhibit sharp phase transitions where cells collectively transition from disordered to ordered states at critical densities. We demonstrate through bio-chemo-mechanical modeling that this emergent behavior arises from a nonmonotonic dependence on nonlinear extracellular matrix (ECM) mechanics: mechanical communication between cells is optimized at intermediate stiffness values where cells can both generate sufficient forces and create strain-stiffened tension bands in the ECM. This balance establishes a critical cell spacing threshold for cell–cell communication ( ∼ 100 to 200 μ m) that is conserved across experimental observations for a broad range of cell types and collagen densities. Our model reveals that the critical stretch ratio at which fibrous networks transition from compliant to strain-stiffening governs this threshold through the formation of tension bands between neighboring cells. These mechanical communication networks drive collective phase transition in tissue condensation when cell density exceeds an effective percolation threshold. Our model explains how microscale cell–ECM interactions control emergent mechanical properties in biological systems and offers insight both into the physics of inhomogeneous materials under active stress, and into potential mechanical interventions for wound healing and fibrotic disorders.